Corruption of Social Assistance Budget during The Covid-19 Pandemic - Amin, Miftahul; Sabisa, Siboyanga; Marilang; Kahfi, Ashabul; Erlina; Istiqamah (Alauddin Law Development Journal (ALDEV), 2024)
The Covid-19 pandemic that hit Indonesia became an opportunity to enrich themselves through corruption of social assistance funds. However, existing regulations do not provide a deterrent effect on the perpetrators. This research is a normative legal research (library research) using a case approach and presented in the form of descriptive analysis. The results of this study indicate that the existence of legal regulations related to corruption during the pandemic has not been fully implemented by Indonesia considering that the Corruption Law, especially Article 2 paragraph (2), is still open to multiple interpretations regarding "certain circumstances". Then the relevance of the Corruption Law to corruption during the pandemic is certainly related to its eradication to provide a deterrent effect even though the sanctions have not been applied. The government then prioritized the data management improvement program.